THE EFFECT OF FLIPPED CLASSROOM LEARNING ON LEARNING OUTCOMES - Abdullah, Walib (Jurnal Kajian Pendidikan dan Psikologi, 2024)
The impact of flipped classroom learning on student learning outcomes is investigated in this study. The research technique is a scientific approach to data collection that aims to accomplish a particular objective. The quasi-experimental research approach will be the methodology employed in this investigation. The following are the variables in this study: The study's independent variable (free variable) is the learning model, specifically the traditional and flipped classroom models. In this study, student learning outcomes are the dependent variable (bound variable). The t-test and One-Way Anova are two examples of the quantitative analysis techniques used in data analysis to process field-sourced data using normality, homogeneity, and hypothesis tests. The significance value table (sig.) illustrates that the post-test value data in the social studies topic is normally distributed, as determined by the computations above. The post-test results indicate a value higher than 0.05, specifically 0.091 in the experimental class and 0.055 in the control class. According to the test requirements, t table = 1.99 and t count = 6.62. As a result, at a level of 0.05, 6.62>1.99, rejecting H0 and accepting Ha. It is possible to conclude that classes using the flipped classroom learning approach have a higher average value on the post-test of geography learning outcomes than classes utilizing the conventional method. With a 5% confidence level (α=0.05), the calculation of F count> F table (45.06> 3.97) indicates that there is a difference in the average value of learning outcomes (there is an influence on learning outcomes). Ho is rejected, while Ha is approved. It is possible to draw the following conclusion from the data analysis results: "The flipped classroom learning paradigm has a positive and significant influence on learning outcomes.